Russia and Iran in Conditions of Economic Sanctions: Anti-Sanction Policy and Resistance Economy - I. P. Khominich; S. Alikhani (Вестник Российского экономического университета имени Г. В. Плеханова)
Economic sanctions always have destructive impact on economic structures of states, especially such developing countries as Iran and Russia. These countries used anti-sanction economic approach in order to oppose western sanctions. Strategy of anti-sanction economy is a tool of counteracting adverse impact of sanctions on national economy as a sanction target. The authors investigate the influence of strategy of anti-sanction economy on national economy of Iran and Russia, which are facing economic sanctions introduced by western countries. Research findings demonstrate that strategy of anti-sanction economy is a key priority of both Iran and Russia. This strategy helps these countries improve the local business climate, support small and medium enterprises and raise efficiency of local production units. Principle recommendations of our research for Iran and Russia imply that apart from using strategy of anti-sanction economy these countries should do their best to lower their dependence on the US dollar (strategy of dollarization), improve bilateral economic cooperation and eliminate trade barriers to increase trade flows.